Lingual orthodontics (Treatment approaches and mechanics): A Review - Anees, Norhan; Kadhom, Zainab Mousa (Scientific Journal of Medical Research, 2021)
Objectives: This review shows the ability of the lingual orthodontic braces in the treatment of most orthodontic problems such as teeth malposition, anteroposterior discrepancies, pre-and -prosthetic surgical cases, and the similarity to some extent in the mechanics that used the labial orthodontic brackets except for some types of treatment techniques. Conclusion: The lingual orthodontic technique is similar to the labial orthodontic technique; they share in the treatment of many orthodontic problems.